Developing the Arabic Textbook from Cultural Understanding/تطوير الكتاب المدرسي للغة العربية على ضوء التفاهم الثقافي - Ifah Uma Faridah; Bakri Mohamed Bkheet Ahmad (Jurnal Al-Maqoyis, 2021)
An effective learning must have a reference as a source of learning, the provision of quality Arabic language-oriented teaching materials in learning is still very rare. This research is motivated need to overcome the gap between ideal conditions and real conditions in the field, especially the problem of the availability of teaching materials with good Arabic culture insight. Textbooks that are used by teachers and students in a lesson, especially Arabic learning, elements of Arabic culture are not paid much attention and only a few are presented in textbooks. The author is interested to research as an effort to fulfill the criteria for the quality of Arabic Language Insight teaching materials based on the view that Arabic Cultural Insights teaching materials are a strategic alternative-accelerated Arabic learning will be better and more effective if supported by good teaching materials as well.Supporting teaching materials with Cultural Insight Arabic have an effect on increasing students' understanding in learning Arabic and are declared accepted. The results of the teacher's assessment of the feasibility of qawā'id teaching materials showed a positive response in the very good category, while the responses given by students to Arabic-oriented teaching materials showed that they could increase motivation, help and facilitate students in learning Arabic.